2022
DOI: 10.1017/aae.2022.13
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Policies and Technical Efficiency of Wheat Production in Kazakhstan and Russia: Evidence from a Stochastic Frontier Approach

Abstract: We utilize a unique primary data set of farms in Russia and Kazakhstan to investigate the link between policy reforms and technical efficiency. These countries have heavily subsidized their domestic agricultural production over the last decade, with a total of around USD 76 billion USD and USD 11.5 billion USD in government funding directed towards the agricultural sectors in Russia and Kazakhstan, respectively. Results of a stochastic frontier analysis make evident that variable inputs, such as fertilizer, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…Studies that have examined the influence of agricultural policy on agricultural efficiency and farmers' income have indicated a positive impact of agricultural policy (El Benni et al 2012). These studies have predominantly utilised econometric models (Johnson et al 1948;Bojnec and Fertő 2022), envelopment analysis (Amores and Contreras 2009;Bai et al 2022), and stochastic frontier analysis (Tleubayev et al 2022;Bernini and Galli 2024), among other approaches. However, these studies have overlooked the impact variations across the types and levels of agricultural policies on diverse regions and types of farmers, in addition to the interactions between agricultural policy and other factors.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Studies that have examined the influence of agricultural policy on agricultural efficiency and farmers' income have indicated a positive impact of agricultural policy (El Benni et al 2012). These studies have predominantly utilised econometric models (Johnson et al 1948;Bojnec and Fertő 2022), envelopment analysis (Amores and Contreras 2009;Bai et al 2022), and stochastic frontier analysis (Tleubayev et al 2022;Bernini and Galli 2024), among other approaches. However, these studies have overlooked the impact variations across the types and levels of agricultural policies on diverse regions and types of farmers, in addition to the interactions between agricultural policy and other factors.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…An association between agricultural production and women's economies is positively correlated in rural areas of developing countries where marginalized women made self-helping groups to finance their crops (Saha & Kasi, 2022). One study showed that the allocation of a loan-loss reserve for insurance companies insuring against agro-climatic change factors improved agricultural production performance due to the effectiveness of relatively low rates of interest (Tleubayev et al, 2022). Access to agricultural credit volume showed that banks provided more loans than microfinance institutions according to the total number of large loans issued for agriculture in Kosovo (Shkodra & Shkodra, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2) The second group is related to credit access and technical efficiency to boost production (Missiame et al, 2021;Rezitis et al, 2003;Shkodra & Shkodra, 2018;Tleubayev et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] also identified the factors influencing the change in food prices in five countries of the world for 2000-2020: the dominant influence of oil prices, a less significant change in the exchange rate. Tleubayev A., Bobojonov I. and Götz L. [10] believe that to increase crop production productivity, instead of state subsidizing farming, other institutional tools should be used: training of farmers, production and marketing cooperation, membership in agricultural holdings, return to cultivation of abandoned land, crop insurance. Jianhua Ye, et al [11] argue that the state should invest more in social development, ecology.…”
Section: Introductionmentioning
confidence: 99%